A diabetologist's perspective of non‐alcoholic steatohepatitis (NASH): Knowledge gaps and future directions. (20th February 2020) - Cusi, Kenneth
Abstract: There is a close link between steatohepatitis (NASH) and Type 2 diabetes (T2DM). Recently, the American Diabetes Association (ADA) recommended screening for NASH and advanced fibrosis in patients with diabetes and hepatic steatosis or elevated plasma alanine aminotransferase (ALT). This is because as many as 30% to 40% may have NASH and 10% to 15% advanced fibrosis. The role of hyperglycemia and the natural history of NASH in diabetes remain poorly understood, as well as which diagnostic algorithm or interventions are most cost‐effective. There is significant clinical inertia and most patients today are still not receiving adequate lifestyle intervention or pharmacological treatment with diabetes agents known to be effective against NASH. Lifestyle intervention improves steatohepatitis in proportion to the magnitude of weight loss, but this trend is not as consistent for regression of fibrosis. This limited success supports the need for concomitant pharmacological therapy. Pioglitazone has been shown to consistently induce resolution of NASH in both patients with or without diabetes in a total of 498 participants in five randomized controlled trials (RCTs), but with modest effects on liver fibrosis. Proof‐of‐concept studies suggest a potential role for GLP‐1RAs and SGLT2 inhibitors. Combination therapy is on the horizon. Treating diabetes and NASH with a combination of pioglitazone, GLP‐1RAs or SGLT2i, could be a cost‐effective strategy to treat both diseases while reducing their high cardiovascular risk. Future combination therapies will likely combine existing diabetes agents with novel NASH‐spechfic drugs under development. This review highlights current knowledge gaps and proposes future directions for the treatment of NASH in diabetes.